iConference 2016 Proceedings
DOI: 10.9776/16305
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Public Awareness of Social Justice Documentary Films based on News Coverage versus Social Media

Abstract: The comprehensive measurement of the impact that information products have on individuals, groups and society is of practical relevance to many actors, including philanthropic funding organizations. In this paper we focus on assessing one dimension of impact, namely public awareness, which we conceptualize as the amount and substance of attention that information products gain from the press and social media. We are looking at a type of products that philanthropic organizations fund, namely social justice docu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The results showed that SVM classifier and the combination of all features are the best predictor of impact in reviews. In another work, the amount of alignment of social media (Facebook and reviews), news articles and the transcript of the film were studied [8]. It was found that social media are more aligned with the main subject of the films.…”
Section: Related Workmentioning
confidence: 99%
“…The results showed that SVM classifier and the combination of all features are the best predictor of impact in reviews. In another work, the amount of alignment of social media (Facebook and reviews), news articles and the transcript of the film were studied [8]. It was found that social media are more aligned with the main subject of the films.…”
Section: Related Workmentioning
confidence: 99%
“…In addition to the semantic network analysis, we employed topic modeling using LDA (latent Dirichlet allocation) to examine the public perceptions and attitudes expressed in the comments. Based on natural language processing, topic modeling is a text summarization technique that identifies salient themes contained in the data (Diesner, Rezapour, & Jiang, 2016). We used the ConText tool.…”
Section: 24 Topic Modelingmentioning
confidence: 99%